Using learning environments for military study - Almeida, Raphael de Souza e; Gonçalves, Thiago; Raposo, Alberto (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
One of the biggest concerns in planning a military operation is how to explore the terrain, avoid collateral damage, and accomplish the mission. During that process, military planners study the topographic and tactical aspects, gathering detailed information to better advise superiors in their decisions. Learning how to prepare for that terrain study takes time and practice, and inside the classroom is difficult. Because of that, sometimes students are taken into regions in a Field Exercise (FE) to understand how to conduct this kind of activity. Even participating in those FEs, it is quite difficult for the instructor to explain to students the subject given the abstraction needed to visualize, for example, the coordination measures for an operation in the area, the company moving to an objective, and so on. Another problem happens when the instructor points to a place and makes observations about that area, while the student accidentally looks at the wrong place and starts learning the content in the wrong way. Trying to solve similar problems, Wenqiong Du et al. developed a Mixed Reality-based platform addressing nontechnical skills personnel for Battlefield First Aid (BFA) training with satisfactory effectiveness. In this work, the interaction between the real and the virtual world was fulfilled by using the HTC VIVE VR Headset. In this context, we propose “Simulador Virtual para Estudo Topotático do Terreno (SVETT),” a simulator that uses resources usually found in classrooms involving 3 interfaces (VR, projection, and constructive) that can help instructors ease teaching the abstract subjects of a terrain study and standardize the knowledge learned from students. The Brazilian Marines Simulation Center developed SVETT and evaluated it with 54 students. The results suggest that using SVETT first, students found participating in the field exercise easier because of their previous contact with the region.